Comparison of Renewable and Non-Renewable Energy in the Long and Short Term of Indonesia Economy - Wahyudi, Heru; Ciptawaty, Ukhti; Ratih, Arivina; Pratama, Ahmad Dhea (International Journal of Energy Economics and Policy, 2023)
Indonesia has established Government Regulation Number 79 of 2014 concerning National Energy Policy (KEN). KEN as a public policy product was determined after going through a "top-down" debate since 2010. KEN's target only focuses on energy supply, even though energy policy has shifted to the side of energy demand. KEN does not set greenhouse gas mitigation targets. To support the achievement of KEN's goals regarding the mix of new and renewable energy (EBT). Indonesia has great potential, but can the potential be maximized by the government in the direction of better and environmentally friendly energy policies. This study analyzes the movement of renewable and non-renewable energy to the Indonesian economy from 1990-2021, using the Error Correction Model (ECM) statistical method by considering short-term and long-term results in the model. long-term results Consumption of non-renewable energy (CFE) has a positive and significant impact on increasing economic growth by 7.14%. Renewable energy in the form of electricity (RE) has a positive and significant influence in increasing economic growth by 0.18%, while the results of renewable energy through water resources (RIF) do not have a positive but not significant impact on Indonesia's economic growth. In the short-term results of the Error Correction Model (ECM), consumption of non-renewable energy (CFE) has a positive and significant effect on increasing economic growth by 5.35%. while the results of renewable energy in the form of electricity (RE) and renewable energy through water resources (RIF) do not have a positive but not significant impact on Indonesia's economic growth during 1990-2021.